Study on the Influence of Split Blades on the Force Characteristics and Fluid–Structure Coupling Characteristics of Pumps as Turbines - Fengxia Shi; Xuexue Zong; Guangbiao Zhao; Denghui Zhang; Pengcheng Wang; Haonan Zhan (Energies)
In order to study the influence of split blades on the turbine force characteristics and fluid–structure coupling characteristics of pumps, this paper selected the IS 80-50-315 centrifugal pump, used as a reverse-acting hydraulic turbine, as the research object, optimized the original pump-acting turbine impeller, and adopted different combinations of long and short blades. Based on the SIMPLE algorithm and RNG k–ε turbulence model, a complete three-dimensional unsteady numerical simulation was conducted on the internal flow field of the pump-turbine. The results show that the split blades reduce the radial and axial forces. The deformation patterns of rotor components in the two pump types used as turbine models were similar, with deformation gradually decreasing from the inlet to the outlet of the impeller. The equivalent stress distribution law of the rotor components of the two pump turbine models has also been found to be similar, with the maximum stress occurring at the connection between the blades and the front and rear cover plates and the minimum stress occurring at the outlet area of the impeller and the maximum shaft diameter of the pump shaft. The maximum deformation and stress of the rotor components in the split blade impeller model were smaller than those in the original impeller model.